THE INFLUENCE OF IWAN FALS AS A CELEBRITY ENDORSER ON TOP COFFEE BRAND IMAGE (Study of College Students at Brawijaya University Malang) - Renaldo M.L. Tobing (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The use of celebrities as part of a marketing strategy is one popular way to support the creation of a brand image (brand image). Selection of celebrity as brand endorser which one of the strategy to built brand image. This study aims to investigate the influence of Iwan Fals as a celebrity endorser on TOP Coffee brand image. This type of research in this research is explanatory research. The data were collected through a questionnaire to college students as consumer TOP Coffee at UB. The sampling technique used was purposive sampling and obtained 150 college students as a sample. To test the hypothesis which is proposed in this study used multiple regression analysis. The results show that the dimensions of the variable celebrity endorser : credibility, attractiveness, expertise, trustworthiness, and match-up product has a significant effect on brand image (Y) with a significance of 0.000 with a coefficient of determination (R2) of 0.446 (44.6 %). While partially, variable credibility, attractiveness, expertise, trustworthiness and product match-up showed a significant effect on brand image. The results of this analysis can be input for the company in terms of marketing strategy, especially TOP Coffee product promotion strategy. Keywords: celebrity endorser, brand image, TOP Coffee